(3JQLeI TjN GdGSdGe GdHdbjfis - (3CHhYHO Gddg eMeO Hf YeQ Hf eMeO GdHZhj, QSdGf,J (B864 (3g` s ((3eMeO Hf Ydi Hf LYaQ Hf eNJGQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LHQ cSQ ef GfUY bdHg daQGb CeHGHg s
(3BNQgG (B:s
(3BNQ GdJQLeI , hGdMeO ddg ChdkG hBNkQG hXGgQkG hHGWfkG s
(3GdeDda YI CNh TjN GdESdGes
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B90 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs